Bentonite and Magnetite Filler-Modified Polyurethane Foam in Fixed Bed Column for the Adsorption of Mercury(II) Ions from Aqueous Solution - Siti Sarah; Adisalamun Adisalamun; Darmadi Darmadi; Suraiya Kamaruzzaman; Abrar Muslim; Saiful Saiful (Aceh International Journal of Science and Technology, 2021)
This paper proposed adsorbent development by synthesizing polyurethane foam (PUF) using a simple method, mixing polyol with isocyanate and adding fillers of bentonite and magnetite to the PUF matrix. The study's main objective was to produce a PUF-based adsorbent with high reactivity to remove Hg2+ in wastewater. This bentonite and magnetite filler-modified polyurethane foam (BMPUF) adsorbent was fixed in a bed column for the adsorption of mercury (II) ions from an aqueous solution. The effect of initial Hg2+ concentration on the removal rate and the effect of contact time on adsorption efficiency was investigated. Langmuir, Freundlich, and BET non-linear models were taken into account to determine the best adsorption isotherm fitting and obtain adsorption capacity, intensity, and pore volume. As a result, it followed the non-linear Freundlich model, and the average adsorption capacity and intensity were 0.466 mg/g and 0.923, respectively. The average BET-based pore volume obtained was 0.782 L/mg. The kinetics study showed that the non-linear pseudo-first-order kinetics model was more suitable for describing the Hg2+ adsorption kinetics. The maximum equilibrium adsorption capacity was 1.770 mg/g with the adsorption rate of 0.0013 min-1 based on the non-linear model. The effect of varying bentonite and magnetite ratio on adsorption isotherm and kinetics was also investigated. Overall, the potential application of BMPUF adsorbent in the adsorption of mercury (II) ions was demonstrated in the current study.